Surgical dental rehabilitation of patients in remission of oncological diseases: assessment of treatment outcomes and quality of life - E. A. Bazikyan; V. V. Arishkova; D. V. Anisimov (LLC "Endo Press", 2023)
Satisfaction with the results of complex dental treatment, and its impact on the quality of life of patients in the conditions of previously conducted complex or combined anticancer therapy.Aim. To assess the change in the quality of life of patients in remission of oncological diseases after complex dental treatment.Materials and methods. Quality of life and aesthetic outcome were assessed using the University of Washington scale (UWQOL) and visual analog scale. The data were analyzed and a comparative evaluation of the results of the main and control groups was carried out.Result. In both groups, different results of satisfaction with appearance and functionality were obtained, patients of the main group demonstrated high rates of chewing function, psychological comfort and comfort when eating in public (p < 0.01).Conclusions. This study proves that surgical dental rehabilitation of patients in remission of oncological diseases with partial or complete absence of teeth allows patients to significantly improve their quality of life.